Effect of subabul (Leucaena leucocephala) canopy, on yield, quality and nitrogen uptake of clusterbean (Cyamopsis tetrogonolsba) and sesame (Sesamum indicum) under agro-silviculture system - O.V.S. iHENUA; R.S. VERMA; T.P. SINGH . * (Indian Journal of Agronomy, 2001)
A f eld experin;ent was conducted during rainy season of 1991 and 1992 to study the effect of subabul (Leucaena leucocephala) canopy management practices and crop gec;metries on seed yield, quality and nitrogen uptake of clusterbean [Cyamopsis tetragonoloba (L.) Taub.] and sesame (Sesamum indicum L.) crops. Topping at 1.50 m system of subabul canopy management gave significantly more yield and better quality of produce. Maximum uptake of nitrogen was also noted under the same system compared with central leader system, open centre system and no lopping conditions.